Is AI More Accurate Than Human Pathologists? The Future of Diagnostic Accuracy in Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Is AI More Accurate Than Human Pathologists? The Future of Diagnostic Accuracy in Digital Health The integration of Artificial Intelligence (AI) into me...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care